2011
DOI: 10.1007/s11218-011-9156-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting children’s liking of school from their peer relationships

Abstract: Prior studies have established that children's peer relationships and school adjustment are associated. The main aims of the current study were to test if four measures of peer relationships (Peer Acceptance, Presence/Absence of Best Friend, Number of Friends, and Perceived Peer Support) could predict School Liking concurrently and longitudinally across a 6 month period, and if gender moderated any of those associations. An opportunistic sample of girls and boys (N = 429 at Time 1 and N = 214 at Time 2) was dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
3
28
0
1
Order By: Relevance
“…The only beneficial factor found to be present in this study is peer relationships, which played a significant role in releasing tension and keeping students wanting to come to school. This is consistent with Boulton, Don, and Boulton (2011) who found that positive peer relationships predict 'school liking'. School principals and teachers should work on supporting peer relationships through activities, projects, competitions, celebrations, and so on.…”
Section: Discussionsupporting
confidence: 90%
“…The only beneficial factor found to be present in this study is peer relationships, which played a significant role in releasing tension and keeping students wanting to come to school. This is consistent with Boulton, Don, and Boulton (2011) who found that positive peer relationships predict 'school liking'. School principals and teachers should work on supporting peer relationships through activities, projects, competitions, celebrations, and so on.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the current study examined school identification, which may assess different aspects of a child's relationship with school such as liking being at school and how much the child feels that others at school are similar to them (Maras, ). This second aspect is different to school liking and school engagement (focussing on on‐task behaviour, orientation, and maturity) examined in previous studies (Betts et al ., ; Boulton et al ., ) which may account for the differing findings. Although children may feel connected to their friends and like school, they may feel different from the majority of children at school.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, reciprocity within best friendships was not significantly associated with identification with school. This contrasted with research reporting links between peer relations and school engagement (Betts et al ., ) and school liking (Boulton et al ., ). The different methodologies employed and the different conceptualizations of school identification, engagement or liking between studies may explain this.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Liking school has been associated with positive peer relationships (Erath et al, 2008). For example, Boulton, Don, and Boulton (2011) discovered that peer acceptance and perceived peer support were significant unique predictors of school liking. Then, negative peer relations, such as peer rejection and negative peer treatment, can in turn have negative effects on school adjustment, i.e.…”
Section: Introductionmentioning
confidence: 99%